2011
DOI: 10.1152/japplphysiol.01064.2010
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide mitigates transition from compensatory hypertrophy to heart failure

Abstract: We reported previously that although there is disruption of coordinated cardiac hypertrophy and angiogenesis in transition to heart failure, matrix metalloproteinase (MMP)-9 induced antiangiogenic factors play a vital role in this process. Previous studies have shown the cardioprotective role of hydrogen sulfide (H₂S) in various cardiac diseases, but its role during transition from compensatory hypertrophy to heart failure is yet to be unveiled. We hypothesize that H₂S induces MMP-2 activation and inhibits MMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 47 publications
3
70
0
2
Order By: Relevance
“…The effects of H 2 S have been attributed to an increase in VEGF expression in the skeletal muscles and VEGFR2 phosphorylation in the neighboring vascular endothelial cells (59). Consistent with the effects of H 2 S in hindlimb ischemia, a recent study (16) reported on the angiogenic effect of H 2 S treatment in myocardial hypertrophy. After H 2 S treatment in an aortic banding-induced pressure-overload mouse model, functional and histological evaluations performed 3 and 8 weeks later revealed that H 2 S supplementation improved cardiac function and the response was associated with a significant increase in capillary density, which mitigated transition from compensatory hypertrophy to heart failure (16).…”
Section: Pan Et Almentioning
confidence: 66%
See 1 more Smart Citation
“…The effects of H 2 S have been attributed to an increase in VEGF expression in the skeletal muscles and VEGFR2 phosphorylation in the neighboring vascular endothelial cells (59). Consistent with the effects of H 2 S in hindlimb ischemia, a recent study (16) reported on the angiogenic effect of H 2 S treatment in myocardial hypertrophy. After H 2 S treatment in an aortic banding-induced pressure-overload mouse model, functional and histological evaluations performed 3 and 8 weeks later revealed that H 2 S supplementation improved cardiac function and the response was associated with a significant increase in capillary density, which mitigated transition from compensatory hypertrophy to heart failure (16).…”
Section: Pan Et Almentioning
confidence: 66%
“…However, as observed by Papapetropoulos et al (48), although H 2 S activates the Akt pathway, it is the MAPK (ERK1/2 and p38) and ATP-sensitive potassium (K ATP ) channel opening pathways, not the Akt pathway, that are involved in H 2 S-stimulated angiogenesis. Consistently, however, H 2 S is reported to mediate angiogenesis through regulation of anti-angiogenic/angiogenic factors production by regulating the matrix metalloproteinase/tissue inhibitor of metalloproteinase axis (16) (Fig. 4).…”
Section: Pan Et Almentioning
confidence: 70%
“…The findings in patients with a low eGFR is reminiscent of the association between higher levels of endostatin and worse outcomes in patients with progressive renal disorders [5,6], potentially reflecting the ability of endostatin to attenuate repair processes after ischemic injury [4,11]. Similarly, endostatin has been suggested to decrease blood supply to the hypertrophied myocardium leading to collagen deposition and fibrosis during experimental HF [12,13]. In contrast, the finding of an association between higher endostatin and better outcomes in patients with preserved renal function could suggest this biological factor may have beneficial effects in some circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…41 Additionally, administration of NaHS in drinking water increased VEGF expression and inhibited angiostatin and endostatin, 2 antiangiogenic factors. 42 Also, the upregulation of both Akt and VEGF may cause this evident angiogenesis phenotype after administration with a H2S donor molecule (SG-1002). 5 H2S also modulates cellular homeostasis by affecting mito- …”
Section: H2s Protection Of Organ Systemsmentioning
confidence: 99%